Microbial traces found in microdolomite associated with seep-related shallow gas hydrate - Shiraishi, Fumito; Akimoto, Takayuki; Tomioka, Naotaka; Takahashi, Yoshio; Matsumoto, Ryo; Snyder, Glen T. (Frontiers in Earth Science, 2023)
Recently, microdolomite grains with a diameter of about 30–150 μm were discovered within seep-related shallow gas hydrate in the eastern margin of the Japan Sea, and the preliminary assumption has been that their formation is mediated by microbially secreted extracellular polymeric substances (EPS). To verify this interpretation, the present study investigates the characteristics of minerals and organic matter inside the microdolomite grains. Observation by polarizing microscopy reveals that the microdolomite grains generally consist of combinations of distinct cores and external cements. The cores are mostly dark or cloudy and their abundance does not show clear depth dependence, while the external cements are generally isopachous in the shallow part and polygonal in the deeper portions. To further clarify the characteristics of these cores and external cements, thin-foil sections were prepared from two major types of microdolomite, one with a dark core and polygonal external cement, and one with a cloudy core and isopachous external cement. These thin-foil sections were then analyzed by scanning transmission X-ray microscopy (STXM) and transmission electron microscopy (TEM). In the dark core, fibriform pores of about 100 nm diameter were observed to be closely related with amorphous calcium carbonate (ACC) and carboxy groups, likely created by heterogeneous nucleation on microbial EPS surfaces. The polygonal external cement is composed of monocrystalline dolomite, representing slow crystal growth in the deeper part where hydrate formation is less active. On the other hand, the observed cloudy core and the isopachous external cement are, respectively, composed of scattered and accumulated rhombohedral dolomite crystals, presumably resulting from homogeneous nucleation in saline pockets of rapidly growing hydrate and subsequent crystal accumulation on the surface of spherical oil films.